(untitled) (Nigerian Journal of Technology, 2016)
In recovery of heavy crude oil by a sufficient means other than thermal recovery methods has been a great concern to researchers. Several researchers have found it difficult to achieve oil in-water (O/W) emulsion stability status. In an effort to minimize the viscosity, heavy crude needs modification. The morphology and stability of oil-in-water emulsions were studied as a function of aqueous phase salinity. In reducing the viscosity of the heavy-oil, brine solutions were selected as alternative in forming oil-in-water (O/W) emulsion. The aim of this research is to investigate the various salinity levels that influence viscosity and stability of oil-in-water emulsion. From observation, the loose emulsions were discovered through bottle test which showed complete separation on low salinity concentration. Optical microscope assembled with a digital camera was used to investigate the oil droplets of the stable and non-stable emulsion. Results indicated that phase separation appears more easily on low concentration at room temperature, and larger size droplets in the high concentrations. Therefore, using low salinity oil in water flooding, it reduces the viscosity of heavy crude oil. http://dx.doi.org/10.4314/njt.v35i2.18